Loss- and gain-of-function analyses of vacuolar protein sorting 2 in Notch signaling of Drosophila melanogaster. - Aoyama, N.; Yamakawa, T.; Sasamura, T.; Yoshida, Y.; Ohori, M.; Okubo, H.; Iida, E.; Sasaki, N.; Ueda, R.; Matsuno, K. (Genes & Genetic Systems, 2013)
Notch signaling is an evolutionarily conserved mechanism that controls many cell-fate specifications through local cell-cell interactions. The core mechanisms of Notch activation and its subsequent intracellular signaling are well understood. Various cellular functions are required for the activation and regulation of Notch signaling. Among them, the endocytosis of Notch and its ligands is important for the activation and suppression of Notch signaling. The endosomal sorting complex required for transport (ESCRT) proteins are required to sort ubiquitinated membrane proteins, such as Notch, into early endosomes. A loss-of-function allele of vacuolar protein sorting 2 (vps2), which encodes a component of ESCRT-III, has been reported. However, this vps2 mutant still produces the N-terminal half of the protein, and its phenotypes were studied in only a few organs. Here, we generated the first null mutant allele of Drosophila vps2, designated vps2², to better understand the function of this gene. In Drosophila wing imaginal discs homozygous for the vps2² allele, early endosomes and multivesicular bodies (MVBs) were enlarged, and Notch and Delta accumulated inside them. As reported for the previous vps2 mutant, the epithelium grew excessively under this condition. We further studied the roles of vps2 by RNA interference-knockdown. These experiments revealed that a partial reduction of vps2 attenuated Notch signaling; in contrast, the loss-of-function vps2 mutant is reported to up-regulate the Notch signaling in eye imaginal disc cells. These results suggest that Notch signaling can be up- or down-regulated, depending on the level of vps2 expression. Finally, we found that vps2 overexpression also resulted in early-endosome enlargement and the accumulation of Notch and Delta. In these cells, a portion of the Vps2 protein was detected in MVBs and colocalized with Notch. These data indicate that the expression of vps2 must be precisely regulated to maintain the normal structure of early endosomes.